Planetary intelligence for sustainability in the digital age: Five priorities - Luers, Amy (One Earth, 2021)
A comment explaining how the digital age has contributed to improve our knowledge of the changing global environment and describing five priority areas where advances are still needed: (1) creating essential actionable insights, (2) building trust; (3) eliminating the digital divide; (4) reimagining global environmental governance; and (5) developing new business models for knowledge generation and management.